IMPLIKASI TEORI BELAJAR KECERDASAN MAJEMUK DALAM PENDIDIKAN AGAMA KRISTEN - Maria Amelia Tana; Agnesia Selan; Maria Indiriani Sesfao; Sofmiarsi Luase; Cindriani Silla; Bendelina Ati Meta; Yohana Ida Goo (JIP: Jurnal Ilmu Pendidikan, 2025)
The purpose of writing is to explore the function of multiple learning theory in Christian religious education learning. Problems in the context of Christian religious education with the lack of approach and understanding of educators towards learning styles and methods, so that in supporting an effective learning process and having an impact on a person's intelligence so that the concept of intelligence of each individual is first brought since birth but in the development of intelligence an individual is obtained where in the learning process there is a multiple intelligence learning theory that provides several types of intelligence that are very useful and solutions for teachers to improve the quality of student learning, the purpose of writing this writing is to provide information and solutions regarding the concept of multiple intelligence and its implications in Christian religious learning, both in the concept of methods and the concept of learning in the classroom, using a qualitative writing method based on literature studies by reviewing, identifying data and information by searching for sources of books, and journals. The results of the writing show the benefits of multiple intelligence learning theory in improving Christian religious education learning so that teachers can explore active learning strategies. Important ideas by outlining each type of intelligence in modifying the learning space according to student comfort in understanding the material.